2012
DOI: 10.1029/2012jc008220
|View full text |Cite
|
Sign up to set email alerts
|

Detailed modeling of recent severe storm tides in estuaries of the New York City region

Abstract: Detailed simulations, comparisons with observations, and model sensitivity experiments are presented for the August 2011 tropical cyclone Irene and a March 2010 nor'easter that affected the New York City (NYC) metropolitan area. These storms brought strong winds, heavy rainfall, and the fourth and seventh highest gauged storm tides (total water level), respectively, at the Battery, NYC. To dissect the storm tides and examine the role of various physical processes in controlling total water level, a series of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 43 publications
6
112
0
Order By: Relevance
“…This means that the model will be nested in other computational models for deriving information needed at the XBeach boundaries. Both a sECOM model (Orton et al, 2012) and a Delft3D-model (Van Ormondt, 2014) will be used and validated at forehand against measurement data. The area of consideration in these models is presented in Figure 4.6.…”
Section: Hydrodynamicsmentioning
confidence: 99%
“…This means that the model will be nested in other computational models for deriving information needed at the XBeach boundaries. Both a sECOM model (Orton et al, 2012) and a Delft3D-model (Van Ormondt, 2014) will be used and validated at forehand against measurement data. The area of consideration in these models is presented in Figure 4.6.…”
Section: Hydrodynamicsmentioning
confidence: 99%
“…Numerous numerical models have been developed and applied to simulate hurricane/typhoon-induced storm surges [6][7][8][9][10][11][12][13][14]. Sheng et al [15] reported that the accuracy of a storm surge simulation depends on many factors including the input data (e.g., bathymetry, topography, and wind/pressure fields), the representation of important processes (e.g., flooding and drying and bottom friction), the model grid resolution, and the open boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Surface winds and pressure data from atmospheric models are input into NHMs to generate water-level forecasts (Shen et al 2005;Di Liberto et al 2011;Orton et al 2012;Georgas et al 2014). For example, Shen et al (2005) used the Advanced Three-Dimensional Circulation Model for Coastal Ocean Hydrodynamics (ADCIRC; Westerink et al 1993) to hindcast the surge for Hurricane Isabel (2003) in Chesapeake Bay and predicted the surge (1.9-2.5 m) to within 0.3 m of the observed surge.…”
Section: A Backgroundmentioning
confidence: 99%